Model Pengaruh Variabel Fasilitas, Harga, Kualitas Bangunan, Lokasi, Pendapatan dan Promosi Terhadap Keputusan Pembelian Rumah Subsidi di Kabupaten Katingan - Noviana Pramesti Putri; Waluyo Nuswantoro; Purwantoro, Almuntofa (Jurnal Serambi Engineering, 2025)
In the context of endeavours to furnish adequate housing, the term "housing" is understood to denote a collection of dwellings situated within a communal environment that has been furnished with amenities, infrastructure, and public facilities. The Indonesian government has implemented a subsidised housing programme targeted at low-income individuals (MBR) to address the nation's housing needs. The objective of this study was to ascertain the extent to which subsidised housing type 36 in Katingan Regency is influenced by facilities, price, building quality, location, income, and promotion.  The present study employs a survey approach, which involves the collection of data from subsidised homeowners through the administration of questionnaires. The study surveyed 100 research respondents. The research data analysis employed structural equation modelling and partial least squares. The findings of the analysis demonstrate that variables such as income, price, location, building quality, and promotion exert negligible influence on purchasing decisions. However, it is evident that facility and promotion variables do have a significant impact on purchasing decisions. The final model demonstrates that the variables studied contribute 80% to the purchase decision, with the remaining 20% influenced by variables not covered in this study. This is evidenced by an R2 value of 0.807.